Interdependence of emotionality, anxiety, aggressiveness and subjective control in handball referees before the beginning of a game: a comparative analysis - Курова, Анастасія Володимирівна; Курова, А. В.; Курова, Анастасия Владимировна; Kurova, Anastasiia V.; Попович, Ігор Степанович; Попович, І. С.; Попович, Игорь Степанович; Popovych, Ihor S.; Коваль, Ірина Андріївна; Коваль, І. А.; Коваль, Ирина Андреевна; Koval, Iryna A.; et al. (Bucharest University Press, 2022)
The purpose of the article is to conduct empirical research on interdependence of the key individual psychological characteristics of handball referees before the beginning of a game; perform comparative analysis of the obtained parameters of referees with different categories and identify significant dynamic changes. The study substantiates and characterizes anxiety, aggressiveness and subjective control as important features of referees’ activity, affecting objectivity of results. Research methods: retrospective critical analysis of scientific literature, psycho-diagnostic testing, purposeful observation, comparative analysis using Student’s t-test, Pearson’s R correlation analysis. The study outlines the primary methodological postulates and technology for measuring parameters of the phenomena under study. Results. The study presents a graphical structure of subjective control of handball referees by qualification categories. Pearson’s (r) correlation analysis allowed determining interdependence of the parameters under study. Positive significant correlations were identified: between emotional stability and internality in the area of achievements (r=.286; p≤.01); between emotional stability and internality in labor relations (r=.278; p≤.01). Negative significant correlations were registered: between internality in the area of achievements and the parameters of aggressiveness: between inclination towards direct physical aggression (r=-.185; p≤.05) and the level of impulsiveness (r=-.268; p≤.01); between self-estimation of reactive anxiety and internality in labor relations (r=-.178; p≤.05). The study substantiates that the identified list of significant correlations proves that a respondent’s achievement of a higher level of qualification requires mobilization of their neural and mental efforts, a high level of subjective self-control and self-regulatory capability. Conclusions. The study emphasizes that the identified correlations of the key individual psychological characteristics of handball referees before the beginning of a game are important scientific facts in the context of the research on referees’ activity. It generalizes that the acquired knowledge should be operationalized into professional qualification upgrade programs for training referees in team sports. The study highlights that the obtained scientific facts can be useful for subjects of competition process, researchers in sport psychology.

Метою статті емпіричне дослідження взаємозалежності ключових індивідуально-психологічних якостей суддів з гандболу перед початком гри; порівняльне аналізування отриманих параметрів суддів різних категорій і встановлення значущих динамічних змін. Обґрунтовано та охарактеризовано тривожність, агресивність і суб’єктний контроль як важливі властивості суддівської діяльності, які впливають на об’єктивність результату. Методи дослідження: ретроспективне критичне аналізування наукової літератури, психодіагностичні тестові методики, цілеспрямоване спостереження, порівняльне аналізування з застосування t-критерію Ст’юдента, кореляційне аналізування r-Пірсона. Окреслено методологічні вихідні положення і технологію виміру параметрів досліджуваних феноменів. Результати. Графічно побудовано структуру суб’єктного контролю суддів з гандболу за кваліфікаційними категоріями. Кореляційним аналізом r-Пірсона встановлено взаємозалежність досліджуваних параметрів. Констатовано позитивні значущі взаємозв’язки: Емоційна Стійкість з інтернальністю в сфері досягнень (r=.286; p≤.01); Емоційна Стійкість з інтернальністю в трудових відносинах (r=.278; p≤.01). Зафіксовано негативні значущі взаємозв’язки: інтернальність у сфері досягнень з параметрами агресивності: Схильність до прямої фізичної агресії (r=-.185; p≤.05) і Рівень нестриманості (r=-.268; p≤.01); самооцінки реактивної (ситуативної) тривожності з інтернальністю в трудових відносинах (r=-.178; p≤.05). Обґрунтовано, що встановлений перелік значущих взаємозв’язків є підтвердженням того, що досягнення респондентом чергового рівня кваліфікації вимагає від нього мобілізації нервово-психічних зусиль, високого рівня суб’єктного контролю і саморегуляційної спроможності. Висновки. Зазначено, що встановлені взаємозалежності ключових індивідуально-психологічних якостей суддів з гандболу перед початком гри є важливими науковими фактами у контексті дослідження суддівської діяльності. Узагальнено, що здобуті знання доцільно операціоналізувати у професійні програми підвищення кваліфікації для підготовки суддів командних видів спорту. Акцентовано, що отримані наукові факти можуть бути корисними для суб’єктів змагального процесу, дослідників психології спорту.
Popovych I. Interdependence of emotionality, anxiety, aggressiveness and subjective control in handball referees before the beginning of a game: a comparative analysis / I. Popovych, A. Kurova, I. Koval, V. Kazibekova, M. Maksymov, V. Huzar // Journal of Physical Education and Sport. - Vol. 22. - Iss. 3. - Bucharest University Press, 2022. - P. 680-689.
Keywords: mental state; reflection; referees’ activity; competition process; psycho-emotional state; sport psychology; психічний стан; рефлексія; суддівська діяльність; змагальний процес; психоемоційний стан; психологія спорту; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology